Migration and Racialization in Times of “Crisis”: The Making of Crises and their Effects - Leila Benhadjoudja, Christina Clark-Kazak, Stéphanie Garneau (Studies in International Development and Globalization, 2025)
The health crisis, the migration crisis, the humanitarian crisis, and the climate crisis. The repeating reference to the idea of crisis to label numerous social upheavals suggests that we now live in a world defined by crisis. Yet the urgency inherent in a crisis often leads to the normalization of rights violations and increased surveillance, profiling and arbitrary arrests, making visible the state’s control over bodies, and certain bodies, in particular. Migration and Racialization in Times of “Crisis” explores the colonial, racist and sexist underpinnings of various declarations of crisis, as well as their effects. Taken together, these contributions show that the state of crisis manifests as a condition for the maintenance of racial and patriarchal capitalism. The English and French version of this title, though distinct, complement each other to offer a more comprehensive and critical look at this approach of “governing through crisis”.